Survey Results for Training and Resource Needs Cited by Early Intervention Professionals in the Field of Visual Impairment. (November 2017) - Ely, Mindy S.; Ostrosky, Michaelene M.
Introduction: Professionals working with infants and toddlers with visual impairments (that is, those who are blind or have low vision) were surveyed regarding their preservice training and their awareness and use of 29 resources related to young children who are visually impaired. Methods: Early intervention visual impairment professionals ( n = 109) from 11 states completed a survey called the Early Intervention Visual Impairment Self-Efficacy Evaluation. The online tool was distributed to all professionals in each target state. Results: Thirty-eight percent of respondents indicated that the preservice program at which they received training as teachers of visually impaired students or orientation and mobility (O&M) specialists did not include content or experiences related to infants and toddlers with visual impairments. In addition, given three types of resources including books and curriculum ( n = 12), websites ( n = 5), and online or "eLearning" courses ( n = 12), websites were rated as most frequently used, and eLearning resources were least frequently used for professional development. Resources on the topic of cortical or cerebral visual impairment (CVI) were more frequently rated as used, compared to resources on topics such as multiple impairments. Discussion: Results demonstrate that some training programs for teachers of visually impaired students and O&M specialists do not include content that prepares professionals to work with infants and toddlers with visual impairments, leaving professionals with a need for additional training to serve this population. In addition, workshops and web-based resources were respondents' preferred means of professional development. Implications for practitioners: As they consider future professional training efforts, individuals responsible for workforce preparation and development in the field of visual impairment need to take into account the training needs and preferred training formats of early intervention professionals.